Performance study of the dual‐stack mobile IP protocols in the evolving mobile internet. Issue 1 (1st January 2015) - Yan, Zhiwei; Wang, Hwang‐Cheng; Park, Yong‐Jin; Lee, Xiaodong
Abstract : The transition from IPv4 to IPv6 is an inexorable trend in the development of Internet. However, since IPv4 has been widely deployed for many years, it is mandatory that the existing IPv4 and the newly deployed IPv6 coexist and interoperate seamlessly. With the study of various mechanisms proposed for the interoperability between IPv4 and IPv6, some mobility management protocols are also extended to work in the mixed mobile Internet. In this study, the authors carry out an in‐depth analysis of three types of standardised mobility management protocols with dual‐stack support. Owing to the difference of underlying basic protocols, their individual dual‐stack extensions have different features and thus are suited for deployment in different scenarios and stages in the evolution of the mobile Internet.